Model Praktik Baik Kepala Sekolah dalam Pengembangan Kemampuan Dasar Guru pada Satuan Pendidikan Sekolah Dasar - Rochaendi, Endi; Ma'mun, Saepul (Alma Ata University Press, 2024)
In carrying out their main duties and functions, school principals still receive critical issues from various circles in the educational ecosystem because they have yet to fully contribute optimally to increasing teacher professionalism. The literature review research aims to identify and analyze several models of good practice implemented by school principals in developing the basic abilities of teachers in elementary school education units. The research findings state that the school principal's good practice model consists of two activities/actions: the Principal as a learning leader and the Principal acting as the creator of the learning environment. The key role of the Principal as a learning leader consists of a servant, role model, expert and instructional leader. Meanwhile, the Principal as the creator of the learning environment is related to his role as a communicator, supporter and manager. These good practices can create a professional, vital teacher profile and construction consisting of passion, vigour, facility, and satisfaction to achieve more productive and competitive learning goals in the educational unit. Keywords: good practice; principal’s; basic teacher abilities